Is there a relationship between level of competition and knowledge in volleyball? - Gil Arias, Alexander; Del Villar Álvarez, Fernando; Claver Rabaz, Fernando; Moreno Domínguez, Alberto; García González, Luís; Moreno Arroyo, M. Perla (FEADEF, 2012)
The main objective of the study was to analyze the relationship between level of competition and declarative and procedural knowledge in young volleyball players. We propose a descriptive/correlational study involving 219 players aged between 14 and 16 years. The level of competition (scholar, regional and national) was the independent variable. Whereas, dependent variables were the two types of knowledge, declarative and procedural, which were measured by filling in two questionnaires. The results show significant differences in knowledge according to the level of competition. Players who participated in national competition show higher levels of declarative and procedural knowledge than those who compete in regional and scholar level. These results reinforce the idea that is the quality of the competition, in which athletes participate, a key factor in the development of the two types of knowledge considered in the investigation